2010
DOI: 10.1097/jom.0b013e3181c5c476
|View full text |Cite
|
Sign up to set email alerts
|

Pricing and Availability Intervention in Vending Machines at Four Bus Garages

Abstract: Objective-To evaluate the effects of lowering prices and increasing availability on sales of healthy foods and beverages from 33 vending machines in four bus garages as part of a multi-component worksite obesity prevention intervention.Methods-Availability of healthy items was increased to 50% and prices were lowered at least 10% in the vending machines in two metropolitan bus garages for an 18-month period. Two control garages offered vending choices at usual availability and prices. Sales data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 17 publications
2
82
0
4
Order By: Relevance
“…They conducted experiments in vending machines where prices of low-fat snacks were reduced by 10, 25 and 50 per cent and found that sales of these products raised by 9, 39 and 93 per cent respectively [40]. These results were duplicated in later studies of the same group [41]. Also, they found that reducing prices of fruits and vegetables with 50 per cent in school canteens lead to a twofold increase in vegetable and four-fold increase in fruit purchases [40].…”
Section: Evidence On the Effectiveness Of Food Pricing Strategiessupporting
confidence: 67%
“…They conducted experiments in vending machines where prices of low-fat snacks were reduced by 10, 25 and 50 per cent and found that sales of these products raised by 9, 39 and 93 per cent respectively [40]. These results were duplicated in later studies of the same group [41]. Also, they found that reducing prices of fruits and vegetables with 50 per cent in school canteens lead to a twofold increase in vegetable and four-fold increase in fruit purchases [40].…”
Section: Evidence On the Effectiveness Of Food Pricing Strategiessupporting
confidence: 67%
“…The Chicago Park District's 100% Healthier Snack Vending Initiative does this by applying nutrition standards consistent with AHA and AHG guidelines. Such approaches can provide opportunities, cues, and support for more healthful behaviors and may be more sustainable than traditional public health approaches focused on individual behavior change (17). Improving access to more healthful foods through machine-vended snacks is a strategy that has demonstrated success in schools and worksites.…”
Section: Discussionmentioning
confidence: 99%
“…Few intervention studies have been conducted using pricing policy thus far. These previous studies suggest that consumers respond to changes in food prices (14)(15)(16)(17)(18) . Although pricing intervention studies showed positive effects, they were limited to a small number of products and were conducted in small-scale settings.…”
mentioning
confidence: 99%